TRAINING OF COMPUTER CONTROL BY USING GAME EEG HEADSET IN PATIENTS WITH PARALYSIS OF LIMBS - JARA, Jan (Journal of Technology and Information Education, 2014)
The article describes the experience of using gaming headset Epoc EEG Headset for practicing control of the computer through mind with patients with limited or no ability to control limbs. This was done in partnership with patients Rehabilitation institute in Kladruby. Describes a method patients' motivation, work progress and results achieved. In the first case study describes a young man who was capable of minimal movement of the head. With G-sensor with high gain could move almost across the screen with the mouse cursor, and using a limited ability to control the facial expression muscles to control mouse buttons. In the second case study describes a patient pre retirement age with limited ability to speak and unilateral paralysis of the limbs. With the motivation and deploy the proposed procedure discovered in himself the ability paralyzed leg after all to control.
Keywords: EEG; Epoc headset; mobility aids; rehabilitation; training; casuistry; motivation; mental mapping control of limbs